HUBUNGAN CVP (COST VOLUME PROFIT) DAN ANGGARAN DALAM PERENCANAAN USAHA - Widaryanti . (STIE Pelita Nusantara Semarang, 2006)
Company is one of economic support in a country. That's company's urgent role for economic development, so that needs open and rational management. Company management needs atool for planning, controlling and decisions making. Cost Volume Profit is a tool for planning and budged canmake more sure sales, production, cost and earning or lose forecast. So that can improve financial statement validity. Cost volume Profit analysis in useful in the very early stageof planing. Cost volume profit (CVP) analysis is method for analyzing the relationships among volume, cost and profit. Manager use these relationships to plan, budget and make dicisions. Planning begins with the setting of general goals proceeds to the cost volume profit analysis of various alternatives, and with preparations of a detailed quantitative plan of action the budget.